A Multiple Case Study Of Integrating Translation Technology Modules Into Undergraduate Translation Programs - Bahri, Hossein (2018)
While the integration of translation technology modules into postgraduate translation programs has increased in recent years, this general trend is not commonly witnessed at the undergraduate level. There are still unresolved questions regarding the types of tools and resources, teaching, learning and assessment activities, the roles and qualifications of teachers, and how these translation technologies should be integrated into the undergraduate curriculum. To answer the above questions, an exploration of these practical issues was carried out from the perspectives of the module teachers and through the analyses of module documents.